Marley & me : life and love with the world's worst dog - Grogan, John, 1957- (LOndon : Hodder, 2008)
The author presents a tender story of his family's love for their yellow Labrador retriever, Marley, and recalls how he grew from a mischievous puppy into a nearly impossible adult that no amount of obedience school training could correct, and of the love they felt for him.
Young Adult
Keywords: Grogan, John, -- 1957-; Grogan, John, -- 1957-; Labrador retriever -- Florida -- Biography; Labrador retrievers